The Reality of Displaced Families "A field study on a sample of displaced families in the city of Aleppo" (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
Syria's war has contributed to the displacement of thousands of families from their areas to other to other regions to looking for security and stability. However, the duration of the war was longer than expected - 8 years and still - which led to the displacement of displaced families from temporary stability in these new areas to semi-permanent stability and the most prominent areas that received displaced families was Aleppo governorate; the number of displaced families (180 thousand) families were displaced from various areas that were subjected to war. They settled in parts of Aleppo city, (18.3%) of the total number of displaced families; So this research came to address the reality of these families through a descriptive study, across three sections, the first section: the problem of research, The second part was the theoretical framework of the research. It dealt with internal migration in Syria before and during the war, through reviewing some of the literature that dealt with the subject, the third section: results. The research included a study of a sample of the displaced families to identify their social reality through a descriptive study, and the study of the need to improve this reality in light of the long period of the war.